2014
DOI: 10.5740/jaoacint.13-425
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Extraction with Ultra-Performance Liquid Chromatography/Tandem Mass Spectrometry for the Determination of Ochratoxin A in Processed Cereal Products

Abstract: A rapid, simple, and reliable method using ultra-performance LC/MS/MS (UPLC/MS/MS) was developed for determination of ochratoxin A (OTA) in processed cereal products. OTA was ultrasonically extracted from the sample with acetonitrile-water (80 + 20, v/v), and the extract was then injected into the UPLC/MS/MS system after filtration. The calibration curves had good linearity with coefficients of determination greater than 0.999. Recoveries of OTA were in the range of 90-104%. LOD and LOQ of OTA in samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…OTA was extracted from a certified reference material (CRM; naturally OTA‐contaminated wheat) as described . Briefly, 20 mL acetonitrile/water (4:1) mixture containing 1 g sample was ultrasonicated for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…OTA was extracted from a certified reference material (CRM; naturally OTA‐contaminated wheat) as described . Briefly, 20 mL acetonitrile/water (4:1) mixture containing 1 g sample was ultrasonicated for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…These ubiquitous fungi are capable of growing and producing OTA at a wide range of temperatures (0–37 °C) and have been found to contaminate agricultural commodities worldwide. Hence, OTA has been found in many raw and processed foods, including cereal grains, beans, coffee, wine, beer, fresh and dried fruits, cocoa, nuts, spices, meats, milk, infant formula, and infant foods, as well as human milk ([ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 61 ]. Among all, cereal grains are the largest contributor of OTA in the diet, representing about 55% of the total OTA intake [ 62 ].…”
Section: Ochratoxin a (Ota)mentioning
confidence: 99%
“…In the case of OTA occurrence in beers, OTA was detected in 12 out of 19 beers (63%) collected from the United States in the range of 0.01–0.27 ng/mL [ 61 ]. De Jesus et al [ 69 ] measured the incidence of OTA in wine collected from the United States and reported that OTA had been detected in 35 out of 41 (85%) of the wines in the range of 0.3–8.6 ng/mL.…”
Section: Ochratoxin a (Ota)mentioning
confidence: 99%